2015
DOI: 10.1002/j.0022-0337.2015.79.11.tb06034.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of an Endodontic Simulation Model for Dental Students

Abstract: The aims of this study were to develop an endodontic simulation model able to implement the electronic method of working length determination (electronic apex locators, EALs) in a dental school, to evaluate the practicality of this tool for dental students, and to compare the accuracy of working length measurements achieved by the EAL and the radiographic method. A new simulation model was constructed by embedding extracted human teeth in a self-cured resin, along with a conductive medium. After radiographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The majority of the students criticised the rate of material removal compared with human teeth, on the grounds that they had already removed caries within natural teeth and knew their removal rate. Wolgin et al used extracted human teeth for their simulation models. However, extracted human teeth have residues of other biological materials, for example gingiva, so they have to be cleaned before use to prevent rot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the students criticised the rate of material removal compared with human teeth, on the grounds that they had already removed caries within natural teeth and knew their removal rate. Wolgin et al used extracted human teeth for their simulation models. However, extracted human teeth have residues of other biological materials, for example gingiva, so they have to be cleaned before use to prevent rot.…”
Section: Discussionmentioning
confidence: 99%
“…Wolgin et al developed and evaluated an endodontic simulation model for practicing the determination of the working length radiographically and endodontically. The model was created by embedding extracted human teeth in a self‐cured resin matrix.…”
Section: Introductionmentioning
confidence: 99%
“…With this system, a student might practise a clinical procedure several times without performing an intervention on a patient . Simulation models have significantly influenced learning in several dental areas, including endodontics, periodontics, dental hygiene and operative dentistry .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies aimed to investigate the perceptions of students concerning innovative 3D printed models and haptic or virtual models . This study is the first one to compare 3D printed models to series models from a student's point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Although industrials have tried to propose models with simulated caries, some of the resulting situations are not realistic, and therefore, some authors have developed their own simulation models for clinical training. Such work has been carried out in various dental fields: endodontic, using natural teeth embedded in resin, implantology or dental surgery . Anderson et al demonstrated all the benefit of 3D printing technology in the field of endodontics, from clinical to educational use .…”
Section: Introductionmentioning
confidence: 99%